1995
DOI: 10.1177/103841119503200305
|View full text |Cite
|
Sign up to set email alerts
|

An Opinion Survey of Performance Appraisal Practices in Hong Kong and the People's Republic of China

Abstract: This paper examines performance appraisal practices as viewed by a sample of 164 Chinese from Hong Kong and the People's Republic of China (PRC). There was a higher tendency for the PRC Chinese to prefer a group orientation to performance appraisal. The PRC sample also expressed a much greater willingness to consider non-performance-related factors and a strongerpreference for open, honest, and direct relations between supervisors and subordinates. In terms of performance attributions, there was no difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Relevant regional differences exist as well; one study found that employees in the People's Republic of China (PRC) tended to desire open, honest, and direct communications from their supervisors, while this was less important to employees in the Hong Kong region (Chow, 1995). Although these findings were published prior to major political changes in the Hong Kong region, cultural researchers have suggested that value and norm differences between this region and the PRC persist (e.g., Dessler & Tan, 2006).…”
Section: Theoretical Explanations Of the Study Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Relevant regional differences exist as well; one study found that employees in the People's Republic of China (PRC) tended to desire open, honest, and direct communications from their supervisors, while this was less important to employees in the Hong Kong region (Chow, 1995). Although these findings were published prior to major political changes in the Hong Kong region, cultural researchers have suggested that value and norm differences between this region and the PRC persist (e.g., Dessler & Tan, 2006).…”
Section: Theoretical Explanations Of the Study Resultsmentioning
confidence: 99%
“…While Shenzhen, where the current study was conducted, is technically part of the PRC, its close proximity to Hong Kong allows the two regions to have close business, trade, and social links and thus it is likely that Hong Kong values and norms transfer over to Shenzhen organizational functioning. Hong Kong has also been described as a region with extremely low uncertainty avoidance values, further suggesting that employees within this society do not have a strong need to know exact reasons and justifications for organizational procedures and outcomes (Chow, 1995;Hofstede, 2001). …”
Section: Theoretical Explanations Of the Study Resultsmentioning
confidence: 99%
See 3 more Smart Citations